Chaotic Oscillator Based True Random Number Generator - Ozcelik, Ahmet Can; Taskiran, Zehra Gulru Cam (IEEE, 2021)
In this study, a CCII+ based chaotic oscillator design, based on a set of chaotic equations that has not been physically implemented before, and a random number generator design, using this analog chaos generator, is realized. The dynamic behavior of the chaotic oscillator has been observed by PSPICE simulations and confirmed by experimental studies. The proposed CCII+ based analog chaos circuit has been used as the entropy source of a true random number generator to show that it can form a basis for different chaotic applications. The designed random number generator has successfully passed the NIST tests.
Keywords: Chaos; Random Number Generation; CCII; RNG; Engineering; Telecommunications